LANGUAGE POLITENESS AND CHARACTER EDUCATION IN INDONESIAN LANGUAGE LEARNING BASED ON CURRICULUM 2013 - Syahrul R. (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2014)
Great nation is a nation that has good character. Being a nation with a good character is the desire of all of us. However, the social situation in our society increasingly alarming. The destruction of moral values​​, the spread of injustice, the proliferation of corruption cases, the erosion of a sense of solidarity, have occurred in our education. Therefore, character education should be encouraged in the Indonesian language learning in schools. Language politeness is identical to the behavior of the character. Polite speech reflects the character's behavior, i.e. behavior that is polite, moral, personality. This paper will discuss the issue of language politeness with learners’ character as well as its implementation in learning. Keywords: m